Dicrostonyx hudsonius - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Dicrostonyx hudsonius (Pallas 1778) [Mus] hudsonius Pallas 1778, Nova Spec. Quad. Glir. Ord.: 208. Type Locality: Canada, Labrador. Vernacular Names: Ungava Collared Lemming. Distribution: NE Labrador, N Quebec, and Belcher Isls in Hudson Bay, Canada. Conservation: IUCN – Lower Risk (lc). Discussion: Unbanded karyotype resembles that of D. richardsoni (see Krohne, 1982); lack of XY-autosomal fusion believed to be primitive within the genus (Borowik and Engstrom, 1993). Relatively early origination, possibly well before the Wisconsin glaciation, proposed from collared lemming stock isolated in periglacial tundra to the southeast of the continental ice sheet (Borowik and Engstrom, 1993; Eger, 1995). Geographic and nongeographic variation evaluated by Eger (1995). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Cricetidae, pp. 955-1189 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 972, DOI: 10.5281/zenodo.7316535